2005
DOI: 10.4072/rbp.2005.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Early Permian chondrichthyans of the Middle and South Urals

Abstract: -Very diverse Early Permian chondrichthyan assemblages occur in the Asselian to Artinskian of the Middle and South Urals. They include numerous symmoriid teeth of "Denaea" decora Ivanov, Cobelodus obliquus sp. nov., Stethacanthus and Denaea; the teeth of the ctenacanthoid Heslerodus; the teeth of the synechodontiform Synechodus antiquus sp. nov.; and the teeth of taxa of doubtful affinities -Adamantina foliacea Ivanov, Cooleyella cf. C. fordi (Duffin & Ward), Cooleyella sp. A., as well the scales and denticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 11 publications
1
42
0
4
Order By: Relevance
“…The recorded gap in the cladodontomorph lineage is almost 50% longer in duration than the gap observed in the coelacanth lineage, and represents the longest gap in the fossil record for an extinct marine vertebrate group. This gap took place after the largest mass extinction of the Phanerozoic 18,19 4,12 (Table 1), the relatively diverse Early Cretaceous assemblage described here was found from outer platform deposits. This fossil record pattern, reminiscent of that observed in the coelacanth lineage from the Late Cretaceous onwards ( Table 1), indicates that some cladodontomorph groups may have survived the end-Permian and the subsequent Triassic-Jurassic mass extinction events by occupying refuge environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recorded gap in the cladodontomorph lineage is almost 50% longer in duration than the gap observed in the coelacanth lineage, and represents the longest gap in the fossil record for an extinct marine vertebrate group. This gap took place after the largest mass extinction of the Phanerozoic 18,19 4,12 (Table 1), the relatively diverse Early Cretaceous assemblage described here was found from outer platform deposits. This fossil record pattern, reminiscent of that observed in the coelacanth lineage from the Late Cretaceous onwards ( Table 1), indicates that some cladodontomorph groups may have survived the end-Permian and the subsequent Triassic-Jurassic mass extinction events by occupying refuge environments.…”
Section: Discussionmentioning
confidence: 99%
“…Before this discovery, the last known unambiguous representatives of the superorder Cladodontomorphii (Symmoriiformes and Ctenacanthiformes, see refs 4,10) were Late Permian in age 4,[11][12][13] . All allegedly Triassic cladodontomoph shark occurrences have been re-evaluated (for example, the Middle Triassic Acronemus tuberculatus 14 ) or have very dubious taxonomic values (Early Triassic fin spines 15 and denticles 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The faunal development was influenced by the increasing transgression respectively the extension of the Palaeo-Tethys Ocean. It can generally be observed that Middle and Late Permian chondrichthyans are less diverse than in the Early Permian (e.g., Malysheva et al 2000, Ivanov 2005). Hybodontoids strongly predominate in the shark assemblages of Middle and Late Permian age, of which several genera survived the Permo-Triassic biotic crisis and became distributed worldwide in the Mesozoic.…”
Section: Discussionmentioning
confidence: 99%
“…-The teeth of Kungurodus from Mechetlino Quarry are only tricuspid. The tricuspid teeth dominate collections from other localities of the South Urals (Ivanov 2005). The five-cusped teeth are quite scarce, and have been found in the Artinskian of the Kazakhstanian Cisurals (Lebedev 2009 (Fig.…”
Section: Kungurodus Obliquus (Ivanov 2005)mentioning
confidence: 99%
“…and the anachronistid neoselachian Cooleyella amazonensis Duffin, Richter & Neis, in addition to a cephalic spine, diverse scales and denticles. K. obliquus was formerly described from the Asselian-Artinskian of the South Urals by the present author as a new species of the genus Cobelodus (Ivanov 2005). This genus was previously known from the Pennsylvanian of USA (Zangerl & Case 1976).…”
mentioning
confidence: 99%